KAJIAN SEJARAH DAN PERKEMBANGAN TEORI EFEK MEDIA - Musfialdy; Ine Anggraini (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
Media is one of the important needs for the community, but the media has an effect on the community both directly and indirectly. In Media Effects Theory three paradigms are used by the media to find out the effects of these media. The first paradigm, called the powerful effects paradigm (Direct Effects Models), the media is said to have enormous power so that members of the isolated and anonymous audience of this mass audience will surrender immediately. The second paradigm is the minimalist effect or the limited effects paradigm (Limited Effects Models), the media seen in audience control over selectivity. The third paradigm of cumulative effects (Cumulative Effects Models), the community has too much potential for media in limited exposure. At present, the research on the theory of media effects has developed sufficiently to the extent of several specific sub-areas of research Key word : Theory of media effects